Evidence for tertiary structural RNA-RNA interactions within the protein S4 binding site at the 5'-end of 16S ribosomal RNA of Escherichia coli.+. - Ungewickell, E (1975)
Evidence is presented for tertiary structural interaction(s) (interactions(s) between two regions of an RNA molecule that are widely separated in the RNA sequence) within the 5'-one third of the 16S ribosomal RNA of Escherichia coli that constitutes the binding site of protein S4. The two main interacting RNA regions were separated by about 120 nucleotides (sections Q to M) of the 16S RNA sequence. A second, smaller gap, of 13 nucleotides, occurred within section C". The two main interacting regions contain about 150 nucleotides (sections H" to Q) and 160 nucleotides (sections M to C"). They are folded back on one another and, especially in the presence of protein S4, are strongly protected against ribonuclease digestion. The intermediate region (sections Q to M), however, is relatively accessible to ribonucleases in the S4-RNP. By partial removal of subfragments from the RNA complex it was possible to localise the two main interacting sites within sections H" - H and sections I" - C". Three main criteria for the specificity of the RNA-RNA interactions were invoked and satisfied. The possibility of other tertiary structural RNA-RNA interactions occurring in other regions of the 16S RNA is discussed. Finally, all the structural information on the S4-RNP is summarised and a tentative model is proposed.